Metacognitive-Based Learning Management System in Natural and Social Sciences: A Study on Enhancing Independence and Critical Thinking Skills - Septiari, Ni Kadek; Gede Wira Bayu (Journal of Education Technology, 2025)
This study was motivated by the low level of independence and critical thinking skills of students in elementary schools, especially in IPAS learning. This research has four main objectives, namely: (1) develop a prototype Learning Management System (LMS) based on metacognitive learning, (2) analyze the content validity of the LMS, (3) evaluate students' responses to the LMS, and (4) measure the effectiveness of the LMS based on metacognitive learning in increasing the independence and critical thinking skills of elementary school students in IPAS content with force material. This research uses the ADDIE development model. The subject of the research is the LMS based on metacognitive learning, while the object of research includes the validity of media content, learning design, material content, student responses, and media effectiveness. Data collection was done through questionnaires and essay questions. The results showed that: (1) the LMS based on metacognitive learning obtained a validity index of 0.995 which is included in the high content validity category, (2) the LMS learning design obtained a validity index of 0.984  with high content validity qualifications, (3) the LMS material content obtained a validity index of 0.986 with high content validity qualifications, and (4) the correlated t-test showed a significance value (2-tailed) of 0.000 or p < 0.05 at the 5% significance level, both for student independence and critical thinking skills. Thus, the LMS based on metacognitive learning is proven to be effective in improving the independence and critical thinking skills of elementary school students.